Wire-arc additive manufacturing of structures with overhang: Experimental results depositing material onto fixed substrate. (August 2022) - Evjemo, Linn Danielsen; Langelandsvik, Geir; Moe, Signe; Danielsen, Morten Høgseth; Gravdahl, Jan Tommy
Abstract: As additive manufacturing (AM) technology grows both more advanced and more available, the challenges and limitations are also made more evident. Most existing solutions for AM build structures layer by layer using strictly vertical material deposition. As each layer must vertically adhere to the previous layer, support structures must be added if there are to be any kinds of overhangs. For methods requiring the build to be performed within a chamber, the size of the structure is also very limited. The research presented in this paper explores possible solutions to these challenges, focusing on wire-arc additive manufacturing in order to effectively build structures that can not easily be constructed using in-box, layer-based methods for AM. By non-vertical material deposition using an industrial robot manipulator, metal structures with overhangs are built onto a fixed, horizontal surface without any support structures. Cross sections of two different structures are examined by optical microscopy and hardness measurements to reveal potential differences between the areas with and without intersections or overhang. Graphical Abstract: ga1 Highlights: Continuous building using WAAM can effectively construct thin-walled structures. Construction of unsupported overhang on fixed, horizontal surface is investigated. Tested set-based control method can build thin-walled structures, but not overhangs. Vertical but skewed material deposition when using WAAM can create small overhangs. Overhangs can be constructed using non-vertical orientation of welding gun.